(untitled) (American Journal of Islam and Society, 1996)
My findings are tentative and subject to further research. This presentation rests on three paradoxes of great relevance to Muslims in the West. The first paradox is that, from the point of views of Muslims in the West, western secularism might be good news and western materialism might be bad news. In other words, western secularism is perhaps a blessing in disguise for Muslims, whereas western materialism is a curse. The second paradox is that recent Republican, rather than Democratic, foreign policy has been more friendly to Muslims, wherea Democratic, rather then Republican, domestic policies are probably more friendly to Muslims. The third paradox concerns the two Islams in the United States: indigenou and immigrant. In the United States, western secularism has protected minority religious groups by insisting on the separation of church and state. This is as major reason why American Jews have been among the greatest defenders of the separation of church and state, for any breach could lead to the imposition of some practices of the religious majority, such as forcing Jewish children to participate in Christian prayers at school. The secular state permits religious minorities to practice their religions in relative peace. Of course, like all doctrines, secularism has its fanatic who sometimes want to degrade, rather than protect, the sacred. But at its best, a secular state is a refuge of safety for minority religions. It is in this sense that western secularism is a friend of Muslims living in the West. But while secularism represents a divorce from formal religion, materialism is a dilution of spirituality. One can be without a formal religion and still be deeply spiritual in a humanistic sense. John Stuart Mill and Bertrand Russell, for example, had no formal religion, yet each had deeply spiritual values. Albert Schweitzer, the Nobel Laureate for Peace and an eventual agnostic, remained deeply committed to the principle of reverence for life, even to the extent of protecting the lives of insects in Africa ...